The Millennium Villages Project: a retrospective, observational, endline evaluation - Shira Mitchell, PhD; Andrew Gelman, ProfPhD; Rebecca Ross, MSPH; Joyce Chen, MSSW; Sehrish Bari, MPH; Uyen Kim Huynh, PhD; Matthew W Harris, MA; Sonia Ehrlich Sachs, MD; Elizabeth A Stuart, ProfPhD; Avi Feller, PhD; Susanna Makela, PhD; Alan M Zaslavsky, ProfPhD; et al. (Elsevier, 2018)
Summary: Background: The Millennium Villages Project (MVP) was a 10 year, multisector, rural development project, initiated in 2005, operating across ten sites in ten sub-Saharan African countries to achieve the Millennium Development Goals (MDGs). In this study, we aimed to estimate the project's impact, target attainment, and on-site spending. Methods: In this endline evaluation of the MVP, we retrospectively selected comparison villages that best matched the project villages on possible confounding variables. Cross-sectional survey data on 40 outcomes of interest were collected from both the project and the comparison villages in 2015. Using these data, as well as on-site spending data collected during the project, we estimated project impacts as differences in outcomes between the project and comparison villages; target attainment as differences between project outcomes and prespecified targets; and on-site spending as expenditures reported by communities, donors, governments, and the project. Spending data were not collected in the comparison villages. Findings: Averaged across the ten project sites, we found that impact estimates for 30 of 40 outcomes were significant (95% uncertainty intervals [UIs] for these outcomes excluded zero) and favoured the project villages. In particular, substantial effects were seen in agriculture and health, in which some outcomes were roughly one SD better in the project villages than in the comparison villages. The project was estimated to have no significant impact on the consumption-based measures of poverty, but a significant favourable impact on an index of asset ownership. Impacts on nutrition and education outcomes were often inconclusive (95% UIs included zero). Averaging across outcomes within categories, the project had significant favourable impacts on agriculture, nutrition, education, child health, maternal health, HIV and malaria, and water and sanitation. A third of the targets were met in the project sites. Total on-site spending decreased from US$132 per person in the first half of the project (of which $66 was from the MVP) to $109 per person in the second half of the project (of which $25 was from the MVP). Interpretation: The MVP had favourable impacts on outcomes in all MDG areas, consistent with an integrated rural development approach. The greatest effects were in agriculture and health, suggesting support for the project's emphasis on agriculture and health systems strengthening. The project conclusively met one third of its targets. Funding: The Open Society Foundations, the Islamic Development Bank, and the governments of Japan, South Korea, Mali, Senegal, and Uganda.